2009
DOI: 10.1007/s00221-009-1761-1
|View full text |Cite
|
Sign up to set email alerts
|

Relation between postural control assessment with eyes open and centre of pressure visual feedback effects in healthy individuals

Abstract: Visual feedback (VFB) of the resultant centre of pressure (CP(Res)) is a potentially interesting technique for rehabilitation purposes. However, all past studies have not been unanimous in supporting its utility in a physical therapy program. The present study was therefore undertaken with the main aim of assessing whether insights from postural control without additional feedback could be gained to explain the possible VFB effects. The CP(Res) displacements of 65 healthy adults were analysed in two conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 33 publications
0
18
2
Order By: Relevance
“…The influence of COP visual feedback on postural control of young and older adults during stance posture has been described before [7][8][9][10]. Dault et al [8] observed that while young adults decreased the COP variability with COP visual feedback, older adults were not able to decrease it.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…The influence of COP visual feedback on postural control of young and older adults during stance posture has been described before [7][8][9][10]. Dault et al [8] observed that while young adults decreased the COP variability with COP visual feedback, older adults were not able to decrease it.…”
Section: Introductionmentioning
confidence: 92%
“…In young adults, the positive effect of COP visual feedback has also been debated. Boudrahem and Rougier [9] observed that only 69% of the adults investigated in their study presented smaller COP displacement during standing with COP visual feedback than in the eyes-open condition. Duarte and Zatsiorsky [10] found that the use of COP visual feedback to reduce postural sway during quiet standing by How aging affects body sway and joint coordination during quiet standing was investigated under two visual feedback conditions provided on a monitor screen: fixed and moving cursor representing the center of pressure (COP) position measured by a platform.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, underestimating maximal torque prior to a training program would likely culminate in D r a f t observations of higher strength gains in exercise interventions. Although the effect of visual feedback on enhancing an MVC is poorly reported, the positive effect of visual feedback on the acquisition of finite motor skills (Horeman et al 2012), postural control (Boudrahem and Rougier 2009) and reducing force fluctuations (Christou 2005) is well known. Thus, the benefit of visual feedback on the execution of MVC is unsurprising; however, its differential effect between agonist-antagonist pairs requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…This property makes this process useful as driving noise in models appearing in finance markets, physics, telecommunication networks, hydrology and medicine etc. (see [2][3][4]). Stochastic differential equations driven by fractional Brownian motion have been considered extensively by research community in various aspects due to the salient features for real world problems (see [5][6][7][8][9][10][11][12]).…”
Section: Introductionmentioning
confidence: 99%